2021
DOI: 10.1016/j.hpb.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and economic outcomes between minimally invasive liver resection and open liver resection: a propensity-score matched analysis

Abstract: Background: Minimally invasive liver resection (MILR) has gained momentum in recent years. This study of contemporary data compares economic and clinical outcomes between MILR and open liver resection (OLR).Methods: We extracted data for patients undergoing liver resection between October 2015-September 2018 from the Premier Healthcare Database. We conducted a propensity score matched analysis to compare complications, in-hospital mortality, inpatient readmissions, discharge to institutional postacute care, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…In addition to having comparable oncologic outcomes and improved immediate postoperative outcomes, MIS is also less costly. A recent study found that in a propensity score matched analysis, minimally invasive liver surgery (MILS) was associated with lower hospital costs ($19 463 vs. $29 119) compared to open liver resections 18 . Currently, MILS is limited to specialized centers, and concerns about the effectiveness and safety once it is disseminated beyond specialized centers is being actively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to having comparable oncologic outcomes and improved immediate postoperative outcomes, MIS is also less costly. A recent study found that in a propensity score matched analysis, minimally invasive liver surgery (MILS) was associated with lower hospital costs ($19 463 vs. $29 119) compared to open liver resections 18 . Currently, MILS is limited to specialized centers, and concerns about the effectiveness and safety once it is disseminated beyond specialized centers is being actively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…invasive liver surgery (MILS) was associated with lower hospital costs ($19 463 vs. $29 119) compared to open liver resections 18. Currently, MILS is limited to specialized centers, and concerns about the effectiveness and safety once it is disseminated beyond specialized centers is being actively investigated.…”
mentioning
confidence: 99%
“…While this data suggest that the robotic platform can be safely utilized with potential bene ts in patients with CRC and CRLM, cost and widespread feasibility are important considerations. Although studies report that MILS is on average less costly than open liver resections ($19,463 vs. $29,119), compared to laparoscopic surgery, robotic surgery has been shown to be more expensive in both isolated colorectal and hepatic procedures [8][9][10][11][12]. No study thus far has compared the costs of a robotic to laparoscopic approach in simultaneous CRC and CRLM resections.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies are worthwhile to review. One of the studies which took a different approach to this comparison was published in 2020 as a comparison of economic and clinical outcomes [ 26 ]. Patients undergoing liver resection from 2015 to 2018 and entered into a database were analyzed with propensity score matching to evaluate complications, in-hospital mortality, readmission rate, discharge to an extended care facility, operating time, length of stay, and total cost.…”
Section: Laparoscopic Hepatic Surgerymentioning
confidence: 99%
“…After matching, laparoscopic liver resection was associated with lower rates of complications (intestinal obstruction: 3.6% vs. 6.0%; respiratory failure: 5.5% vs. 10.9%; bleeding: 8.2% vs. 17.4%; and pleural effusion: 1.9% vs. 4.9%), in-hospital mortality (0.5% vs. 3.0%), 90-day readmission (10.4% vs. 14.3%), discharge to extended care facility (6.9% vs. 12.3%), operating time (257 vs. 308 min) hospital length of stay (4.3 vs. 7.2 days), and hospital costs (USD 19,463 vs. USD 29,119) (all p < 0.001). The authors conclude that laparoscopic hepatic resection is associated with a lower risk of complications and reduced resource utilization compared with open liver resection [ 26 ].…”
Section: Laparoscopic Hepatic Surgerymentioning
confidence: 99%